Эпизоотологическое значение большого баклана в Азово-Черноморском регионе - Русев, И.Т.; Греков, В.С.; Нехороших, З.Н.; Могилевская, З.И.; Маликова, М.В. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
We investigated a mixed colony of the Cormorant and herons nested on the willows in reed-beds of the Lower Dnieper. Virus of a fever of the Western Nile was isolated (on the suckers of white mice) from the mosquitoes collected at the study area (mainly mosquito Culex pipiens). The isolation of arbovirus from the carriers confirms its circulation in this biotope.